Strategies for Strengthening Business Agility through Business Ecosystems in Culinary MSMEs in Regency - Lutfia, Lutfia Nurhakim; Fatah M, Galih Abdul; Sapril M, Teten Mohamad Sapril M Mohamad (Entrepreneurship Faculty, Universitas Garut, 2024)
This study is intended to test and analyze the effect of business ecosystem on business agility (survey on culinary micro, small and medium enterprises in Garut Regency). Micro, small and medium enterprises have a very fast role in increasing economic growth. Findings reveal that operations, research and development, transformation, and strategy are important dimensions in business agility. The purpose of this study was to determine the effect of business ecosystem on business agility in small and medium culinary businesses in Garut Regency. The population in this study were culinary micro, small and medium enterprises in Garut Regency. This type of research is explanatory survey research using a quantitative approach. The sample used in this study was 399 respondents, then processed using SPSS statistic 26 using purposive sampling technique. The analytical tools used in this research are simple linear regression, instrument test, classical assumption test, and hypothesis testing. The results of this study state that the business ecosystem variable has an influence of 62.8% on business agility. The conclusion from the results of this study is that the ability in business agility is very necessary and cannot be separated from bringing together harmony between ecosystem components in a company.